Pengaruh Intensitas Aset Tetap dan Intensitas Persediaan terhadap Tarif Pajak Efektif - Pratiti, Dian; Sari, Eka; Ningsih, Widya; Holiawati, Holiawati (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2024)
This research is a quantitative study that aims to determine how fixed asset intensity, inventory intensity on effective tax rates in food and beverage manufacturing companies listed on the Indonesia Stock Exchange in 2019-2021. The number of samples in this study was 22 companies, with the sample withdrawal method using the purposive sampling method. This study uses secondary data obtained from the annual report of the company. Data analysis using panel data regression, which consists of descriptive statistical analysis, classical assumption test.Panel data regression model selection and hypothesis testing. The results of data analysis or panel data regression show that the inventory intensity variable partially has a positive effect on the effective tax rate. While the fixed asset intensity variable has no effect on the effective tax rate. At the same time, fixed asset intensity, inventory intensity has a significant effect on the effective tax rate.